2015
DOI: 10.1371/journal.pntd.0003669
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of Mass Drug Administration for Lymphatic Filariasis in Zanzibar in 2006: Was Transmission Interrupted?

Abstract: BackgroundLymphatic filariasis (LF) is targeted for elimination through annual mass drug administration (MDA) for 4–6 years. In 2006, Zanzibar stopped MDA against LF after five rounds of MDA revealed no microfilaraemic individuals during surveys at selected sentinel sites. We asked the question if LF transmission was truly interrupted in 2006 when MDA was stopped.Methodology/Principal FindingsIn line with ongoing efforts to shrink the LF map, we performed the WHO recommended transmission assessment surveys (TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 17 publications
3
44
1
Order By: Relevance
“…For example, due to successful control efforts over the past decades, the number of malaria cases has drastically declined [1, 2], the Tsetse fly has disappeared [3], and the transmission of lymphatic filariasis has been reduced to very low levels [4, 5]. Also urogenital schistosomiasis that imposed a considerable public health problem and formerly occurred with a very high prevalence on both islands [611], is now targeted for elimination [1214].…”
Section: Introductionmentioning
confidence: 99%
“…For example, due to successful control efforts over the past decades, the number of malaria cases has drastically declined [1, 2], the Tsetse fly has disappeared [3], and the transmission of lymphatic filariasis has been reduced to very low levels [4, 5]. Also urogenital schistosomiasis that imposed a considerable public health problem and formerly occurred with a very high prevalence on both islands [611], is now targeted for elimination [1214].…”
Section: Introductionmentioning
confidence: 99%
“…The high variation in mf prevalence after a given number of treatment rounds within districts, as observed in Ghana (this study) and elsewhere [5-7] complicates decision making. If communities with high residual mf prevalence are by chance not included in surveys, MDA may be stopped prematurely with danger of resurgence [5]. This could be prevented by targeting pre-TAS surveys to communities at high risk of residual transmission.…”
Section: Discussionmentioning
confidence: 86%
“…Additional 30 countries have delivered MDA at least once in all endemic areas and are also on track to achieve elimination [4]. While many have passed the TAS, there are also reports of failure [5] and of ongoing transmission in spite of passing the TAS [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…As of 2018, of the total 256 endemic districts where MDA was implemented in India [3], 97 districts had passed TAS 1 and stopped MDA; 27 had cleared TAS 1 and 2; TAS 1 was proposed in 16 and in the remaining districts MDA is being continued. In spite of achieving Mf prevalence of <1% in these districts, studies in India and elsewhere have shown the existence of transmission foci [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%